2013
DOI: 10.3892/mmr.2013.1680
|View full text |Cite
|
Sign up to set email alerts
|

An oncolytic adenovirus expressing interleukin-24 enhances antitumor activities in combination with paclitaxel in breast cancer cells

Abstract: Abstract. Oncolytic adenoviruses are a novel class of anticancer treatment, based upon their ability to replicate selectively within malignant cells resulting in cell lysis. The replication-selective adenovirus, ZD55-IL-24, was constructed by harboring an E1B-55 kDa deletion and arming with interleukin-24 (IL-24). The microtubule-stabilizing drug paclitaxel (PTX) exhibits activity in relapsed cancer. In the present study, the synergistic antitumor effects of the combination of PTX and ZD55-IL-24 on breast canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…IL-24 inhibits the growth of breast [ 64 ] and lung [ 65 ]cancers. It is also reported that IL-24 induces apoptosis in melanoma cells [ 66 ], and enhances antitumor activities when applied in combination with paclitaxel in breast [ 67 ] and prostate [ 68 ] cancers. Recombinant human IL-24 (rhIL-24) reverses the chemoresistance in human breast cancer cell line MCF-7 cells [ 69 ] and significantly suppresses the growth of ovarian cancer cell [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…IL-24 inhibits the growth of breast [ 64 ] and lung [ 65 ]cancers. It is also reported that IL-24 induces apoptosis in melanoma cells [ 66 ], and enhances antitumor activities when applied in combination with paclitaxel in breast [ 67 ] and prostate [ 68 ] cancers. Recombinant human IL-24 (rhIL-24) reverses the chemoresistance in human breast cancer cell line MCF-7 cells [ 69 ] and significantly suppresses the growth of ovarian cancer cell [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, combination of oncolytic adenovirus expressing IL-24 with chemotherapeutic agents dramatically enhanced the cytotoxic effects through induction of apoptosis against cancer of the breast, colon, liver, lung, brain, pancreas, and melanoma [110,114-123]. In yet another study, treatment of hepatocellular carcinoma (HCC) cells in vitro with IFN-alpha in combination with an oncolytic adenovirus expressing IL-24 (SG600-IL-24) resulted in tumor cell apoptosis.…”
Section: Reviewmentioning
confidence: 99%
“…21,22 In this study, basing on the previous research, we constructed fiber chimeric adenovirus vectors, in which the fiber protein of 5-serotype adenovirus (Ad5) was substituted by that of 35-serotype adenovirus (Ad35), aiming to facilitate the infection for renal cancer cells. The expression of the cell surface proteins (CAR, correlated with Ad5 infection and CD46, correlated with Ad35 infection) had been investigated in the cultured renal cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%